(untitled) (Research, Society and Development, 2022)
The Cyclodextrins are cyclic oligosaccharides, where they are used as pharmaceutical excipients and have the following functions: perform the inclusion complex, solubility, stability, improve the organoleptic characteristics of the drug, and among other versatilities. However, cyclodextrins are also called for the treatment of neurodegenerative diseases: Alzheimer’s, Parkinson’s and Niemann Pick C1, because the available therapy is not on the market and is quite limited and ends up being a challenge for medicinal chemistry to produce new drugs. The objective of the study is to carry out a review of the narrative literature, with the aim of observing the possible therapeutic activities of cyclodextrins that could be used effectively in neurodegenerative disorders. The databases used were: Scielo, PubMed, Science Direct and LILACS. Studies carried out with hydroxypropyl-B-cyclodextrin, showed non-profile changes in the affected cells.. As well, the future expectations are promising, tracing the CDs, not just as an excipient, but as an active pharmaceutical input (IFA), improving or delaying these actions and expanding innovation to treatment.